2021
DOI: 10.1371/journal.pone.0256146
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating artisanal fishing of globally threatened sharks and rays in the Bay of Bengal, Bangladesh

Abstract: Sharks and rays are at risk of extinction globally. This reflects low resilience to increasing fishing pressure, exacerbated by habitat loss, climate change, increasing value in a trade and inadequate information leading to limited conservation actions. Artisanal fisheries in the Bay of Bengal of Bangladesh contribute to the high levels of global fishing pressure on elasmobranchs. However, it is one of the most data-poor regions of the world, and the diversity, occurrence and conservation needs of elasmobranch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 93 publications
(120 reference statements)
0
28
0
Order By: Relevance
“…We found Himantura uarnak in the VU category of the global Red List [48], and in our PSA study, it showed low vulnerability (V = 1.56). The species is mainly exploited by artisanal fishing gear, i.e., modified drift gill nets, set bag nets, hooks, and long lines [8,59]. Harpadon nehereus, was listed as an NT species in the global Red List (IUCN, 2021), whereas it showed low vulnerability in our analysis (V = 1.25) and was largely caught by set bag nets, seine nets, and gill nets [60].…”
Section: Comparison Of Species' Vulnerability With Other Assessmentsmentioning
confidence: 87%
See 2 more Smart Citations
“…We found Himantura uarnak in the VU category of the global Red List [48], and in our PSA study, it showed low vulnerability (V = 1.56). The species is mainly exploited by artisanal fishing gear, i.e., modified drift gill nets, set bag nets, hooks, and long lines [8,59]. Harpadon nehereus, was listed as an NT species in the global Red List (IUCN, 2021), whereas it showed low vulnerability in our analysis (V = 1.25) and was largely caught by set bag nets, seine nets, and gill nets [60].…”
Section: Comparison Of Species' Vulnerability With Other Assessmentsmentioning
confidence: 87%
“…The weighted average data quality scores of productivity attributes and susceptibility attributes for the identified species fell under the moderate-low categories and moderate quality categories, respectively. Data on the life history traits and stock assessment of the identified species from the Bay of Bengal and adjacent waterbodies have not been adequately analyzed [8,56]. The majority of the data for productivity attributes were categorized as "very limited", and for susceptibility attributes, the majority of the data were categorized as "best" (Figure 3b) since the fishery-specific information was collected from the relevant sources of shrimp trawl fishery, alongside the current comprehensive state of the stocks in the Bay of Bengal, which had an impact on species' vulnerability analysis performed through the semi-quantitative approach [57,58].…”
Section: Vulnerability Assessment By Productivity Susceptibility Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The latter provided flexibility to explore subjects important to individual respondents on an informal level, helping to characterize the system qualitatively. Stakeholder-specific semi-structured questionnaires to evaluate: (1) fishing practices; (2) target and by-caught species and their value; (3) legal frameworks governing fishing activities and compliance to these; and (4) the attitude of fishers toward conservation measures were designed partially based on Jabado et al (2015), ., and Haque, Cavanagh, and Seddon (2021); . In some instances, related questions were grouped together (e.g., questions regarding the value or species) to aid both the information gathering and analysis.…”
Section: Interview Surveysmentioning
confidence: 99%
“…Sustainable elasmobranch fisheries are possible, and a number of developed countries manage some elasmobranch fisheries sustainably (e.g., School Shark, Galeorhinus galeus ; Gummy Shark, Mustelus antarcticus ; Alaskan Skate, Bathyraja parmifera in the USA and Australia) (Prince, 2005; Dulvy et al, 2017; Simpfendorfer & Dulvy, 2017). However, the sustainable management of these fisheries is underpinned by data, enabling effective monitoring and assessment, and a good understanding of the fishery, together with high levels of compliance to regulations (Prince, 2005; Dulvy et al, 2017; Simpfendorfer & Dulvy, 2017; Dulvy et al, 2021; Haque, Cavanagh, & Seddon, 2021). Despite initiatives such as the UN Food and Agricultural Organization (FAO) to develop sustainable management plans for elasmobranchs (https://www.fao.org/ipoa-sharks), many developing countries face challenges resulting from limited research and resources (e.g., Bornatowski et al, 2014; de Mitcheson et al, 2018; Haque et al, 2020; Haque, Cavanagh, & Seddon, 2021; Haque, D'Costa, et al, 2021; Haque, White, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%